International review of cell and molecular biology. - Galluzzi, Lorenzo (International Review of Cell and Molecular Biology ;, 2018)
International Review of Cell and Molecular Biology, Volume 337 reviews and details current advances in cell and molecular biology. The IRCMB series has a worldwide readership, maintaining a high standard by publishing invited articles on important and timely topics that are authored by prominent cell and molecular biologists. Sections in this new release include the karyosphere (karyosome) and its peculiar structure of the oocyte nucleus, organoids as models of disease, lipid droplets as organelles, the dark side of apoptosis, interconnections between autophagy and secretion, and the regulation and function of intracellular pressure in cell biology.